PROFILE OF THE FARMERS UNDER MISSION KAKATIYA PROGRAMME IN TELANGANA STATE - and D. SRINIVASA CHARY, K. ARUNA, V. SUDHA RANI, I. SREENIVASA RAO, G.E.CH.VIDYASAGAR (The Journal of Research, PJTSAU, 2021)
A study was conducted to know the profile of the farmers under Mission Kakatiya programme. Telangana state was selected purposively, two districts (Karimnagar and Kamareddy) from Northern Telangana zone, Mahabubnagar and Nalgonda from Southern Telangana zone and Siddipet and Badradri Kotthagudem from Central Telanganaa zone) were selected purposively from each zone. From each district two tanks (one from beneficiary village and one from non-beneficiary village) were selected. A total of 360 (180 beneficiary farmers and 180 non-beneficiary farmers) farmers from 12 tanks were considered as sample for the study. Profile characteristics viz. age, education, farm size, farming experience, extension contact, information seeking behavior, mass media exposure, empathy, socio – politico participation, scientific orientation, economic motivation, achievement motivation and extent of participation in tank irrigation management were selected for the study. Experimental research design was followed. Majority of the beneficiary farmers belonged to categories of middle age (55.00%), primary school education (40.56%), Small farm size (38.34%), medium level of farming experience (50.00%), extension contact (45.56%), information seeking behaviour (51.67%), mass media exposure (48.33%), empathy (42.78%), socio-politico-participation(49.44%), scientific orientation (54.44%), economic orientation(47.78%), achievement motivation (43.89%) and Extent of participation in tank irrigation management(53.33%). With respect to non – beneficiaries, majority of the farmers belonged to categories of middle age (52.78%), primary school education (35.56%), small farm size (43.89%), medium level of farming experience (44.44%), extension contact (50.00%), information seeking behaviour (44.45%), mass media exposure (45.56%), socio-politico-participation (45.56%), scientific orientation (43.89%), economic orientation (43.33%) and achievement motivation(38.88%) and low level of empathy (45.00%) and extent of participation in tank irrigation management(43.33%).